2016
DOI: 10.12688/f1000research.7202.2
|View full text |Cite
|
Sign up to set email alerts
|

A paradoxical relationship between Resveratrol and copper (II) with respect to degradation of DNA and RNA

Abstract: Resveratrol (R), a plant polyphenol, is known to reduce Cu (II) to Cu (I) generating reactive oxygen species that can cleave plasmid DNA. Here we report a surprising observation of a paradoxical relationship between R and Cu whereby plasmid DNA cleaving / degrading activity of R-Cu increased progressively as the ratio of R to Cu was increased i.e., the concentration of Cu was successively reduced with respect to a fixed concentration R. Whereas cleavage of plasmid DNA occurred at low molar ratios of R to Cu, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Light metals, such as Zn, are not active when combined with resveratrol (unpublished data). The DNA degrading activity of R-Cu is maintained even when the molar concentration of Cu is reduced more than 10,000 fold with respect to that of R [24]. We have also shown that R-Cu is active in vivo, and can degrade the DNA component of cfCh thereby inactivating it even when the molar ratio of R:Cu is kept at 1: − 10 000 [20,25].…”
Section: Preparation Of Cfch Inactivating Agents Their Sources Dosamentioning
confidence: 68%
“…Light metals, such as Zn, are not active when combined with resveratrol (unpublished data). The DNA degrading activity of R-Cu is maintained even when the molar concentration of Cu is reduced more than 10,000 fold with respect to that of R [24]. We have also shown that R-Cu is active in vivo, and can degrade the DNA component of cfCh thereby inactivating it even when the molar ratio of R:Cu is kept at 1: − 10 000 [20,25].…”
Section: Preparation Of Cfch Inactivating Agents Their Sources Dosamentioning
confidence: 68%
“…It has been reported that resveratrol acts as a pro-oxidant in presence of copper 10 which is another widely researched nutraceutical 11 . Resveratrol can reduce copper (II) to copper (I) thereby generating highly unstable free-radicals 10 which can degrade cell-free chromatin 7, 12-14 and can lead to prevention of endotoxin sepsis in mice 7 . The pro-oxidant activity of resveratrol-copper is maintained even when the molar concentration of copper is reduced 10,000 fold 7, 12-14 .…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol can reduce copper (II) to copper (I) thereby generating highly unstable free-radicals 10 which can degrade cell-free chromatin 7, 12-14 and can lead to prevention of endotoxin sepsis in mice 7 . The pro-oxidant activity of resveratrol-copper is maintained even when the molar concentration of copper is reduced 10,000 fold 7, 12-14 . Doses of resveratrol and copper taken by the patients included in this analysis were nearly 50 times and 2000 times less, respectively, than those currently recommended as health supplements 15, 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the analysis of the effect of chemicals and drugs on DNA and proteins, in the presence of iron and copper is very important and interesting for many researchers. In contrast to the drugs such as Resveratrol (26), bleomycin (27), chloramphenicol (28), N-acetylcysteine (29) and procarbazine (30), bezafibrate, even at high concentrations, did not cause any breakage in a supercoiled plasmid in the presence of iron or copper. In contrast, bezafibrate could protect supercoiled pUC19 plasmid DNA against damaging hydroxyl radicals generated by Fenton reactions.…”
Section: Discussionmentioning
confidence: 90%